Cosmopolitan cadmium hyperaccumulator Solanum nigrum: Exploring cadmium uptake, transport and physiological mechanisms of accumulation in different ecotypes as a way of enhancing its hyperaccumulative capacity. (15th October 2022) - Dai, Huiping; Wei, Shuhe; Twardowska, Irena; Hou, Nan; Zhang, Qing
Abstract: The non-essential element cadmium (Cd) is one of the most problematic priority soil pollutants due to multitude of pollution sources, mobility in the environment and high toxicity to all living organisms. This strongly limits also the number and occurrence of species – Cd hyperaccumulators to be used for soil phytoremediation. However, efficient Cd hyperaccumulator Solanum nigrum L. appeared to commonly occur worldwide as a representative of Solanum nigrum complex of a great taxonomic diversity. This led to the idea that the search among different ecotypes of Solanum nigrum L. may result in the identifying the most efficient Cd hyperaccumulator without applying to soil any additional measures such as chemical ligands. In this first pioneering comparative study, three randomly selected ecotypes of S. nigrum L. ssp. nigrum from Shenyang (SY) and Hanzhong (HZ) in China, and Kyoto (KY) in Japan were used in pot experiments at soil treatments from 0 to 50 mg Cd kg −1 . The Cd accumulation capacity appeared to represent KY > HZ > SY range, KY ecotype accumulating up to 73%, and HZ ecotype up to 67% bigger total Cd load than SY ecotype. At Cd content in soil up to 10 mg kg −1, no significant effect on the all ecotype biomass, photosynthetic activities, contents of first line defense antioxidant enzymes (CAT, SOD, GPX), and scavenging antioxidants ASA, GSH, was observed. At Cd in soil>10 mg kg −1 all these parameters showed decreasing, and cell damage indicator MDA increasing trend, however total accumulated Cd load further increased up to 30 mg kg Cd in soil in all ecotypes in the same KY > HZ > SY sequence. The study proved the great potential of enhancing Cd accumulation capacity of S. nigrum species by selecting the most efficient ecotypes among commonly occurring representatives of S. nigrum complex worldwide. Moreover, these first comparative experiments convinced that the cosmopolitan character and great variety of species/subspecies belonging to Solanum nigrum complex all over the world opens the new area for successful soil phytoremediation with the use of the most appropriate eco/genotypes of S. nigtum as a tool for the best Cd-contaminated soil management practice. Graphical abstract: Image 1 Highlights: Cosmopolitan character of S.nigrum allows to search for the best Cd hyperaccumlators S. nigrum ecotypes show different Cd accumulation capacity and response to stress Long-distance flow rate from root to leaves plays the major role in Cd accumulation GPX activity in ecotypes shows the strongest differentiated response to Cd stress Antioxidant contents in S.nigrum are >10-fold bigger than in Solanum non-accumulators